Some aspects of the etiopathogenesis of acute pancreatitis - Varela, Nelson B; Gateño, Nisso (Cirugía del Uruguay, 1970)
The results of the initial studies on duodenal distention as a possible etiology of acute pancreatitis are reported. The procedures performed, the experiencies and the conclusions obtained after these preliminary studies are described.